Diagnostic test accuracy of presepsin and interleukin-6 in neonatal sepsis: A systematic review and meta-analysis - Puspita Sahu, Elstin Anbu Raj Stanly, Leslie Edward S. Lewis, Krishnananda Prabhu, Mahadev Rao, Vijayanarayana Kunhikatta, Krishnakumar Athavil (Journal of Applied Pharmaceutical Science, 2025)
The study aimed to compare the diagnostic accuracy of interleukin-6 (IL-6) and presepsin in neonatal sepsis. The was evaluated by exploring databases such as PubMed, cumulative index to nursing and allied health literature, excerpta medica database, and Scopus. The data extraction and reporting were done in accordance with preferred reporting items for systematic review and meta-analysis of diagnostic test accuracy studies checklist, while quality assessment tool of diagnostic accuracy studies-2 tool was applied for risk of bias evaluation. The Spearman’s correlation test was employed to analyze the heterogeneity by threshold effects whereas, by nonthreshold effects were assessed through Higgins I2 statistics. A hierarchical model was employed to estimate the sensitivity, specificity, positive and negative likelihood ratio (PLR, NLR), and diagnostic odds ratio (DOR). Additionally, the hierarchical summary receiver characteristics (HSROC) curve was plotted to evaluate the accuracy of these biomarkers. Following the screening procedure, four articles were identified. The respective Spearman’s correlation coefficient for presepsin and IL-6 were −0.44, p = 0.600, and 0.600; p = 0.400, with the I2 value of 75.7% and 92%, respectively. The summary sensitivity and specificity of presepsin were 0.859 (0.808−0.898) and 0.902 (0.731−0.969), while that of IL-6 was 0.893 (0.806–0.944) and 0.852 (0.508–0.970). Meanwhile, the area under the curve (AUC) of HSROC curve showed presepsin to have better AUC than IL-6, i.e., 0.9305 and 0.9190, respectively. Evidence suggests presepsin to be more accurate diagnostic biomarker than IL-6.
Keywords: Neonatal sepsis, presepsin, interleukin-6, systematic review, meta-analysis